Formation of pale purple coneflower (Echinacea pallida (Nutt.) Nutt.) seed productivity in the conditions of the Left-Bank Forest-Steppe of Ukraine - Pospielov, S.; Pospielova, G.; Zezekalo, Ye.; Onipko, V.; Manachynskyi, O. (Scientific Progress & Innovations, 2025)
The study results of seed productivity of pale purple coneflower (Echinacea pallida (Nutt.) Nutt.), a promising medicinal and honey crop are presented. The research was conducted in the conditions of production plantations of Poltava region. It was established that at the early stages of ontogenesis, pale purple coneflower developed slowly: the first sprouts appeared 11–15 days after sowing and this period extended to 20–25 days. The cotyledon leaf phase lasted about for 7–9 days, and the first true leaf was formed during 25–32 days. The above-ground part and root system grew slowly in the first two months, their development accelerated from July. By the end of the vegetation, the plant formed a rosette of leaves and a fleshy vertically thickened rhizome. The generative period of pale purple coneflower began from the second year of growing season. Flowering lasted on the average for 46–52 days, starting in June. Plants reached a height of 85 cm, forming from 1 to 9 generative stems (on the average – 5.4). The average number of seeds per plant made 2770 pieces, and thousand-seed weight varied within 2.3–3.55 g. The morphometric study of the parameters of different orders’ inflorescences on the shoot shows that the anthodia of the first-fourth orders were characterized by the largest diameter (3.02–3.60 cm) and the height of the inflorescences (2.44–3.25 cm). The first three inflorescences provided 68 % of the total seeds’ weight from the plant, which indicates their highest productivity and value. It is emphasized that the sowing qualities of pale purple coneflower seeds are limited by a long period of organic dormancy. Laboratory germination of freshly harvested seeds from inflorescences of the first order did not exceed 60%, but of inflorescences of the second and third orders was 75–78 %. Infectious structures of five fungi genera (Alternaria, Cladosporium, Fusarium, Mucor, Stachybotrys) were found on the achenia. To increase germination, it is recommended to conduct stratification at a temperature of +4–5°C for at least 60 days. It was concluded that seed crops of pale purple coneflower can be used more rationally by harvesting inflorescences of the fourth and higher orders for pharmaceutical needs. Taking into account the biological characteristics of the crop will contribute to increasing the yield and ensuring the stable cultivation of this promising plant.